Hukum Nikah Mut’ah: Analisis Pemikiran Jumhur Ulama dan Syiah Imamiyah - Robiah Robiah; Agus Supriadi; Irfan Bakti; M. Maulidiyan Syah (Simpati, 2023)
Mut'ah marriage has become a phenomenon that has reaped pros and cons from Jumhur Ulama and Shia circles. This is because the Jumhur Ulama scholars do not allow mutah marriages and it is forbidden, while the Shia allow mutah marriages. Both have reasons that come from understanding the verses of the Koran and the hadith of the Prophet Saw. Therefore, analytical efforts are needed to find out the law of mut'ah marriage. This research uses a library research method which aims to collect books, journals and sources related to the research title. From the data in the form of books and journals collected, the author then tries to analyze and compare the existing differences. This research aims to find out the thoughts of Sunni and Shia ulama regarding mut'ah marriage. Apart from that, this research aims to analyze and compare the thoughts of Sunni and Shia ulama based on the postulates which form the basis of the arguments of both parties. From the analysis efforts carried out by the author, several explanations were produced, namely: 1). Jumhur Ulama still forbids and does not allow mut'ah marriages; 2). Imami Shiites allow mut'ah marriage and actually recommend it; 3). The law on mut'ah marriage is divided into two, namely halal according to Shia and haram according to Jumhur Ulama.